2013
DOI: 10.5194/bg-10-6391-2013
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between elevated <i>p</i>CO<sub>2</sub> and temperature on the Antarctic sea ice diatom <i>Nitzschia lecointei</i>

Abstract: Abstract. Polar oceans are particularly susceptible to ocean acidification and warming. Diatoms play a significant role in sea ice biogeochemistry and provide an important food source to grazers in ice-covered oceans, especially during early spring. However, the ecophysiology of ice-living organisms has received little attention in terms of ocean acidification. In this study, the synergism between temperature and partial pressure of CO 2 (pCO 2 ) was investigated in relationship to the optimal growth temperatu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 50 publications
4
41
1
Order By: Relevance
“…These results are complementary to a recent short-term study where no change in specific growth rate was detected in N. lecointei after 14 days exposure to 960 matm pCO 2 at 21.88C, although increased pCO 2 had a positive effect on growth at higher temperatures [9]. Another recent short-term study also concluded that natural sea ice algal communities could be very tolerant to changes in pCO 2 and pH [22].…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…These results are complementary to a recent short-term study where no change in specific growth rate was detected in N. lecointei after 14 days exposure to 960 matm pCO 2 at 21.88C, although increased pCO 2 had a positive effect on growth at higher temperatures [9]. Another recent short-term study also concluded that natural sea ice algal communities could be very tolerant to changes in pCO 2 and pH [22].…”
Section: Discussionsupporting
confidence: 59%
“…Antarctic sea ice algae are known to have widespread range of carbon concentrating mechanisms (CCMs) [8] that facilitate carbon fixation [9]. Furthermore, up to 40% of marine phytoplankton primary production is generally released as dissolved organic carbon (DOC) [10], although values over 70% have been observed [11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations